Determinants of Non-Performing Loans: A Case Study of Commercial Banks Listed on The Amman Stock Exchange for The Period (2022-2011) - Maaiteh, وسام عبدالحميد (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
The study aimed to measure the impact of the determinants of non-performing loans in commercial banks listed on the Amman Stock Exchange for the period (2011-2022). The study sample consisted of (12) commercial banks. The study included the following independent variables: , i) banking determinants: return on equity, loan loss provision ratio, capital adequacy ratio, bank size, and ii) economic determinants: inflation rate, unemployment rate, while the dependent variable was the ratio of non-performing loans to total loans. The researcher used cross-sectional data models, fixed and random effects models, to test the study hypotheses. The results of the study showed that there is a statistically significant negative effect of the return on equity rate and capital adequacy ratio, and bank size on the ratio of non-performing loans to total loans. On the other hand, the study showed that there is a statistically significant positive effect of the loan loss provision ratio, inflation rate, and unemployment rate on the ratio of non-performing loans to total loans. The study recommended that Jordanian commercial banks should improve their profitability in order to increase their ability to create sufficient provisions to meet non-performing loan losses.